2018
DOI: 10.1002/gj.3387
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical and Sm–Nd isotopic evidence for the composition of the Palaeoproterozoic crust of the West African Craton in Ghana

Abstract: The metasedimentary rocks of the Sefwi and Lawra volcanic belts in Ghana respectively were analysed for their major and trace elements and Sr‐Nd isotopic compositions to constrain the provenance, palaeo‐weathering conditions, and tectonic setting of the rocks. Geochemical characteristics of the metasedimentary rocks show low to moderate chemical weathering in their source regions and the rocks are interpreted to have been derived from mixture of mafic and felsic rock components. The LREE show much enrichment i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 54 publications
(107 reference statements)
2
3
0
Order By: Relevance
“…The calculation indicates that the Birimian shales in the Wa‐Lawra Belt received at least 80% of its detritus from juvenile Palaeoproterozoic Terrane. This interpretation is fairly consistent with earlier works carried out on the Birimian sedimentary rocks of the Kumasi Basin (Asiedu et al, 2017) and the Sefwi Belt (Sakyi et al, 2019) that suggest that sediments received at least 90% of its detritus from a juvenile Birimian volcanic arc. Roddaz et al (2007), however, reported that the Birimian sedimentary rocks from the Djibo greenstone belt, Burkina Faso, received 60–100% of its detritus from a juvenile Birimian volcanic arc.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The calculation indicates that the Birimian shales in the Wa‐Lawra Belt received at least 80% of its detritus from juvenile Palaeoproterozoic Terrane. This interpretation is fairly consistent with earlier works carried out on the Birimian sedimentary rocks of the Kumasi Basin (Asiedu et al, 2017) and the Sefwi Belt (Sakyi et al, 2019) that suggest that sediments received at least 90% of its detritus from a juvenile Birimian volcanic arc. Roddaz et al (2007), however, reported that the Birimian sedimentary rocks from the Djibo greenstone belt, Burkina Faso, received 60–100% of its detritus from a juvenile Birimian volcanic arc.…”
Section: Discussionsupporting
confidence: 92%
“…The interpretations that the Birimian shales were predominantly derived from the juvenile Birimian volcanic rocks and deposited in an arc setting are consistent with the interpretations of earlier provenance studies of Birimian sedimentary rocks carried out by Asiedu et al (2004, 2017, 2019), Roddaz et al (2007) and Sakyi et al (2019).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations